Relevant muscle selection for needle electromyography examination in polio survivors - Fidancı, Halit; Öztürk, İlker; Arlıer, Zülfikar (The European Research Journal, 2021)
Objectives: Needle electromyography (EMG) has an important role in the diagnosis of poliomyelitis. Since needle EMG is a painful and time consuming procedure, selecting the most effective muscles for needle EMG is important. We aimed to determine the clinically or subclinically affected regions in polio survivors by examining the minimum number of muscles with EMG. Methods: Polio survivors with weakness in at least one limb were included in this retrospective cohort study. The extremities were divided into two groups: 1) Group 1: The extremities with Medical Research Council score of ≤ 1 in at least one muscle, 2) Group 2: Clinically unaffected or mildly to moderately affected extremities that do not meet the criteria of Group 1. The needle EMG findings of the muscles were analyzed. Results: Twenty-nine polio survivors were included in the study. Needle EMG findings of 352 muscles were reviewed. Needle EMG findings in 57 lower extremities and thirty-two upper extremities were analyzed. There was no upper extremity meeting the criteria of Group 1. Thirty-eight lower extremities were included in Group 1. The amplitudes and durations of motor unit action potentials (MUAPs) were not different between the muscles of the Group 1 lower extremities (p > 0.05). Among the muscles of Group 2 upper and lower extremities, the amplitude and duration of MUAPs were higher in the deltoid and the vastus lateralis muscles compared to the other muscles, respectively (p = 0.002 and p = 0.003 for upper extremity muscles; p = 0.005 and p < 0.001 for lower extremity muscles). Conclusions: Using the needle EMG findings, an algorithm was made to determine the affected regions. Thus, the affected regions can be identified by applying needle EMG to a minimum number of muscles.